Nonprofit Organizations: The Impact of Advertising in Fundraising - Agaraj, Xhiliola; Pjero, Elenica; Sokoli, Ylldes; Ramaj, Aurela (Richtmann Publishing, 2013)
Managers in many nonprofit organizations in the World have adopted a marketing approach. In nonprofit organizations,marketing tactics are used to build the organizations image and reputation in society and help the public remember theorganization and its cause. Marketing tactics help differentiate one nonprofit from another nonprofit that is offering similarprograms, and are used to attract and retain donors, clients, and volunteers. Advertising is one of the marketing tactics whichis used from nonprofit organization to inform, persuade, and remind target publics (donator, clients, volunteers) about theorganization and its offers. The aim of the paper is to study the situation of non-profit organizations in Albania, the impact ofadvertising to attract different donors, and to verify the hypothesis: